Activation cross section of the (n,2n) reaction on Hf isotopes - Kalamara, A.; Serris, M.; Spiliotis, A.; Sigalos, D.; Patronis, N.; Kokkoris, M.; Diakaki, M.; Axiotis, M.; Lagoyannis, A.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
Cross sections of the 174Hf(n,2n)173Hf and 176Hf(n,2n)175Hf reactions have been experimentally determined relative to the 27Al(n,α)24Na reference reaction at incident neutron energies of 15.3 and 17.1 MeV by means of the activation technique. The irradiations were carried out at the 5 MV tandem T11/25 Accelerator Laboratory of NCSR "Demokritos" with monoenergetic neutron beams provided via the 3H(d,n)4He reaction, using a new Ti-tritiated target of 373 GBq activity. In the determination of the 176Hf(n,2n)175Hf reaction cross section the contamination of the 174Hf(n,γ)175Hf and 177Hf(n,3n)175Hf reactions has been taken into account. Moreover, the neutron beam energy has been studied by means of Monte Carlo simulation codes and the neutron flux has been determined via the 27Al(n,α)24Na reference reaction.